TEXT AND BIBLE CANONIZATION: Discussion of the Confession of the Bible Canon and Its Implications for the Church - Dapot Damanik; Lasmaria Nami Simanungkalit (Sekolah Tinggi Teologi Moriah, 2022)
God uses the Bible as a means of introducing himself in a special way (a special revelation to people who want to believe). The writers of this Bible are human beings who at the time of writing have been or are being controlled by the Holy Spirit. Even though they did the writing for a specific purpose, these writings were history for the next generation, giving advice, making poetry but in the end the canon team found that the writing was authoritative as the word of God. The importance of textual alignment and canonization of the Bible is due to the many interpretations of various theological circles. The purpose of this study is to discuss the text (books) and the canonization of the Bible and how it implies for Christians. The method in this research uses a qualitative approach with a literature study in the field of systematic theology. The result is that the determination of the canon is very important, because in this way the church states frankly, that the future of God's revelation begins in the Old Testament and ends in the New Testament. The canon of the Bible is central to the life of a Christian, because it is related to the scriptures. Tuhan memakai Alkitab Sebagai sarana dalam memperkenalkan diri secara khusus (penyataan khusus kepada manusia yang mau percaya). Para penulis dari Alkitab ini adalah manusia yang saat melakukan penulisan telah atau sedang dikuasai oleh Roh Kudus. Walaupun mereka melakukan penulisan tersebut untuk tujuan tertentu, tetapi tulisan-tulisan tersebut mensejarahkan kepada generasi berikut, memberikan nasehat, membuat syair tetapi pada akhirnya tim kanon menemukan bahwa ternyata tulisan tersebut berwibawa sebagai firman Tuhan. Pentingnya pelurusan terhadap teks dan kanonisasi Alkitab disebabkan oleh banyaknya interpretasi berbagai kalangan teologi. Tujuan Penelitian ini adalah mendiskusikan teks (kitab-kitab) dan kanonisasi Alkitab dan bagaimana implikasinya bagi umat Kristen. Metode dalam penelitian ini menggunakan pendekatan kualitatif dengan studi literatur bidang teologi sistematika. Hasilnya adalah penetapan kanon tersebut sangat penting, sebab dengan demikian gereja menyatakan dengan berterus terang, bahwa masa depan penyataan Tuhan diawali dalam Perjanjian Lama dan telah diakhiri dengan Perjanjian Baru. Kanon Alkitab merupakan hal yang sentral dalam kehidupan orang Kristen, karena hal tersebut berkaitan dengan kitab suci.